Meningkatkan Pemahaman Perencanaan Karir Peserta Melalui Bimbingan Klasikal Dengan Menggunakan Peta Konsep - Rizki Soya Intani; Intan Prastihastari Wijaya; Ayu Febri Eka Putri (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Lack of understanding related to career planning will affect the process of making career decisions for the future and career planning as a way to prepare and equip students to be ready and mature to face various challenges regarding careers in the future. The results of observations conducted in class X 12 SMA Negeri 7 Kediri showed a lack of understanding of career planning. This research was conducted as an effort to improve students' understanding of career planning through classical action services. By using concept map. The research was conducted with three meetings, pre-action, cycle I and cycle II. Each cycle was carried out with the same stages, namely planning, action, observation and reflection. The research subjects were students of class X 12 totaling 36 students. The results of the questionnaire analysis showed an increase in the understanding of career planning of students indicated by the average value at pre-action 63%, then in cycle I increased to 68% and in cycle II 73% which means effective in improving career planning with concept maps in students